(Literature Review) Pengembangan Sistem Informasi Puskesmas yang Terintegrasi Untuk Meniningkatkan Pengambilan Keputusan Kesehatan - Eko Khair Anthony; Lismardani Lismardani; Eka Yan Fitri; Budi Harton; Alfani Ghutsa Daud (Journal of Innovative and Creativity, 2025)
Integrated health information systems in community health centers (Puskesmas) face various challenges, one of which is in the decision-making process. To improve the quality of services and the efficiency of managing health information systems, an appropriate and effective approach is essential in supporting decision-making. This study is a literature review. The data sources for this literature review were obtained from ScienceDirect and Google Scholar. The research data were collected from the years 2018 to 2025. Based on the literature review, the development of integrated information systems encounters several challenges, including fragmentation, poor data quality, limited human resource capacity, and inadequate management. Fragmentation occurs due to the vast amount of data spread across various systems and health institutions, while poor data quality is caused by a lack of training, insufficient investment in information technology infrastructure, and poor coordination between health agencies. To address these challenges, improvements can be made through enhanced information technology infrastructure, staff training at Puskesmas, increased human resource capacity, and better data integration. In addition, education and training for healthcare workers and administrative staff at Puskesmas need to be improved so that they are capable of using health information systems effectively.